Aedes koreicus, a vector on the rise: Pan-European genetic patterns, mitochondrial and draft genome sequencing - Kornélia Kurucz; Safia Zeghbib; Daniele Arnoldi; Giovanni Marini; Mattia Manica; Alice Michelutti; Fabrizio Montarsi; Isra Deblauwe; Wim Van Bortel; Nathalie Smitz; Wolf Peter Pfitzner; Christina Czajka; et al. (PLoS ONE, 2022)
Background The mosquito Aedes koreicus (Edwards, 1917) is a recent invader on the European continent that was introduced to several new places since its first detection in 2008. Compared to other exotic Aedes mosquitoes with public health significance that invaded Europe during the last decades, this species’ biology, behavior, and dispersal patterns were poorly investigated to date. Methodology/Principal findings To understand the species’ population relationships and dispersal patterns within Europe, a fragment of the cytochrome oxidase I (COI or COX1) gene was sequenced from 130 mosquitoes, collected from five countries where the species has been introduced and/or established. Oxford Nanopore and Illumina sequencing techniques were combined to generate the first complete nuclear and mitochondrial genomic sequences of Ae. koreicus from the European region. The complete genome of Ae. koreicus is 879 Mb. COI haplotype analyses identified five major groups (altogether 31 different haplotypes) and revealed a large-scale dispersal pattern between European Ae. koreicus populations. Continuous admixture of populations from Belgium, Italy, and Hungary was highlighted, additionally, haplotype diversity and clustering indicate a separation of German sequences from other populations, pointing to an independent introduction of Ae. koreicus to Europe. Finally, a genetic expansion signal was identified, suggesting the species might be present in more locations than currently detected. Conclusions/Significance Our results highlight the importance of genetic research of invasive mosquitoes to understand general dispersal patterns, reveal main dispersal routes and form the baseline of future mitigation actions. The first complete genomic sequence also provides a significant leap in the general understanding of this species, opening the possibility for future genome-related studies, such as the detection of ‘Single Nucleotide Polymorphism’ markers. Considering its public health importance, it is crucial to further investigate the species’ population genetic dynamic, including a larger sampling and additional genomic markers.